Attitudes and perceptions towards research among final year medical students in a private medical college of coastal Karnataka: A cross-sectional study - Kini, Sanjay; R., Muthukumar; Maiya, Rakesh G.; K., Nishanth Krishna; Kiran, N. Udaya (Journal of Health and Allied Sciences NU, 2017)
Introduction: Research experience gained by medical students during their under graduate tenure plays a significant role in their future endeavours in the field of medical research. The present study was a cross-sectional study conducted to know the attitudes and perceptions towards research among final year medical students in a private medical college.Methods: A total of 220 students participated in the study.Results: The majority of the students agreed that research is important in the medical field (88.6%, 195/220). The majority also believed that research methodology to be part of medical curriculum (72.7%, 160/220). 31.8% (70/220) felt that Research methodology will be helpful to enter competitive exams (USMLE, PLAB). The barriers for conducting research as believed by students were: Lack of interest (32.7%, 72/220), Lack of time (31.4%, 135/220), Inadequate knowledge about research methodology (51.4%, 113/230), Lack of guidance by faculties (27.7%, 61/220), Lack of research curriculum (34.1%, 75/230) Inadequate facilities for research (35.5%, 78/220), Inadequate financial support (30.9%, 68/220) and others 2.9% (6/220). Of the participating students, 23.2% (51/220) participated in research during medical school, while 76.8% (179/220) did not.Conclusion: Medical colleges should emphasize more on research among the undergraduate students. There is a need to reform the medical curriculum with more weightage towards research methodology.
Keywords: Attitudes; research; coastal Karnataka